Post occupancy evaluation (POE) on energy management practices in public universities towards sustainability / Alia Abdullah Saleh, Noorazlina Kamarulzaman and Siti Zubaidah Hashim - Abdullah Saleh, Alia; Kamarulzaman, Noorazlina; Hashim, Siti Zubaidah (2012)
Nowadays, universities can be considered as ‘small cities’ occupying large land area, growing populations and traffics, and the various complex activities which are not limited to education and research activities alone. The issues of sustainability become world-wide and global issue. Every univeristy is built to serve the tertiary education to the students based on the various activities offered involving students as the dominant occupants of universities campus. Therefore, the design and facilities provided in the universities must suit the objectives of the education activities resulted in two significant ways; which are direct and indirect impacts on the conditions, environment and sustainabality. The increasing number of students and inefficient of energy use and these may decrease the total performance system of the building year by year. Facilities and energy managers are also hungry for guidance to help them develop a long term approach to energy and cost savings. Post Occupancy Evaluation (POE) is one of strategic analyses of building sustainability after occupancy. Information of the building’s condition is gained by reviewing what the occupants’ feelings are and how they response to their needs by using and occupying the building. Seeing this importance, the evaluative criteria derived from the occupants of the educational buildings need to be measured in terms of the quality of the building facilities for its general condition and suitability for educational purposes. The educational process and learning activities may be interrupted due to the poor building conditions. Hence, there is a need to adopt the application to evaluate the performance of the technical aspects of the universities building.